African Innovations in Harnessing Farmer Assets as Collateral - Chapoto, T.; Aboagye, A.Q.Q. (Emerald Publishing Limited, 2017)
Purpose The purpose of this paper is to document and appraise two innovations by which nontraditional forms of collateral are being used to make smallholder crop and livestock farmers bankable in Ghana and Zimbabwe. Design/methodology/approach The setup and operations of the warehouse receipt system (WRS) in Ghana were evaluated for the extent to which the WRS was meeting crop farmers’ expectations and the WRS’s own objectives. Owners of the WRS, a certified warehouse operator in a big city, and two operators of certified community warehouses in farming communities were interviewed. Two focus group discussions with crop farmers were also held. Information about the setup and operations of the Tawanda Nyambirai Livestock Trust (TNLT) Private Limited in Zimbabwe (TNLT) and extent of serving the credit needs of livestock farmers was obtained by telephone from the managing director. Data were gathered in April 2014 and were analyzed later. Findings Due to low output no smallholder farmer targeted by the WRS had been issued with a tradable certified warehouse receipts to serve as collateral to potential lenders. Grain aggregators (non-farmers) have aggregated enough grains from farmers to be issued warehouse receipts. Grain farmers report substantial reduction in post-harvest losses when they lodge farm proceeds with certified community warehouses. For the TNLT, more than 140 farmers had deposited 700 cattle and had been issued with tradable certificates of deposit within one year of TNLT to obtain revolving credit from one bank. Other benefits and challenges are highlighted. Originality/value Both approaches have potential of helping to solve liquidity constraints of farmers.
Keywords: Credit; Collateral; Crop and livestock farmers; Warehouse receipt system; Cattle bank